EBSD study of strain dependent microstructure evolution during hot deformation of a typical nickel-based superalloy. Issue 2 (15th November 2018) - Zhang, Hongbin; Qin, Shengxue; Li, Huiping; Liu, Jie; Lv, Yuting; Wang, Yan; Zhang, Peng; Zhou, Haiping; Wu, Tao
Abstract: Abstract : The microstructure evolution of a typical nickel-based superalloy was studied in the strain range of 0.1–0.9 at 1110 °C/0.01 s −1 by using the electron backscattered diffraction technique. It was found that the evolution of recrystallized microstructures, grain boundary characteristics, and textures was closely related to strain level. With the increasing strain level, the fraction of equiaxed dynamic recrystallization (DRX) grains increased significantly at the expense of the large non-recrystallized grains, and there was a decrease in total low angle grain boundaries fraction and a simultaneous increase in the fraction of high angle grain boundaries. In addition, the occurrence of DRX promoted the formation of Σ3 boundaries, and the coherent Σ3 boundaries were much easier to form at the strain above 0.5. On the other hand, 〈100〉 component of the textures became stronger with the increasing strains, and the lack of 〈111〉 orientations can also be observed in the textures at high strains above 0.7.